(untitled) (Economics and region, 2023)
Today, in the conditions of a full-scale war on the territory of Ukraine, one of the key aspects of the development of the health care sector is the provision of access to medical care and medical services, as well as the provision of personnel potential and reform of the health care system. Therefore, the assessment of the influence of factors on the development of the health care sector is important for the study of the state and trends in the field of health care. It was determined that the following general factors influence the development of the health care sector: the level of funding of the health care sector; level of demand for medical services; the quality of medical services and the efficiency of the health care system; innovations in medicine; economic situation in the country; political situation in the country; environmental factors; global trends and international relations. A group of social and demographic factors has been outlined and they include: the general state of health of the population and the level of its morbidity; extending the life expectancy of the population; age distribution of the population; population mortality rate and its causes; population migration, gender distribution of the population; population birth rate. It has been established that over the last year the number of deaths is greater than live births. That is, in recent years, population depopulation has been taking place in Ukraine. The analysis of statistical data showed that the first recorded cases of death due to cardiovascular diseases are more than 60% of the total number of the deceased population, although there was a decrease in the incidence of the population for the main classes of diseases. Next in order of decrease due to neoplasms is 10.6% in 2022. And over the past two years, mortality due to the Covid-19 infection has been -12%. Mortality due to other causes ranges from 3% to 5%. The analysis of social and demographic factors confirms their significant influence on the development of the health care sector. It is outlined that the assessment of socio-demographic factors will provide an opportunity for a certain improvement not only of the state of health of the population, but also opportunities for strategic planning of the development of the health care sector.